A Case Study with a Riverside Community to Improve Apps Instant Payments Access - Teran, Luciano Arruda; Silva, Alan Trindade De Almeida; De Carvalho, Caio Pinheiro; Farias, Sandy Hiorrana Lima; Dos Santos, Suzane Santos; Araujo, Fabiola Pantoja Oliveira; De Souza, Cleidson Ronald Botelho; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Computational systems have revolutionized essential services to society. The inaccessibility of instant payment applications can cause obstacles in financial activities between customers. This work aims to improve the accessibility of instant payment services for emergent users. We carried out a case study in a riverside community with 12 participants using the Semiotic Engineering theory (SemEng) across the Communicability Evaluation Method (CEM), identifying the accessibility problems caused by communicability disruptions. Data collection has been organized in three steps: interviews about social aspects, interactions with a payment proposal, and interviews to gather interaction challenges and opportunities. The payment proposal was developed with accessibility guidelines, a report, and manuals of a Brazilian financial institution. With this, we developed 14 design considerations for instant payment applications, which software developers can easily and quickly implement. Lastly, we highlighted the social, regional, and geographic factors that shape the digital interactions of emergent users.